P Pemanfaatan Alat Pengendali Hama Wereng Coklat Menggunakan Spray Otomatis dan Lampu LED di Desa Sumbersari - Mohamad Dimyati A; Devit Suwardiyanto; Halil Halil (J-Dinamika : Jurnal Pengabdian Masyarakat, 2021)
The staple food of the Indonesian population is rice. Farmers in the process of planting rice have several obstacles, including: weather factors, availability of fertilizers, pests and diseases. One of the main pests of rice plants is the brown planthopper. Brown planthoppers attack almost all rice varieties with damage levels ranging from mild to severe and can even cause crop failure. Planthoppers have the ability to reproduce in large numbers in a short time. The planthopper sucks the liquid from the rice plant, causing the plant to grow stunted and yellow, then the leaves turn yellow and dry, like burning. Farmers eradicate planthoppers by spraying insecticides. The planthopper habitat is at the base of rice planting, making planthoppers difficult to eradicate using spraying techniques. Characteristics of planthoppers attracted by lights at night, can be used to eradicate planthoppers. The brown planthopper pest control device is designed to use automatic spray and LED lights. The LED light serves to attract the planthoppers closer to the automatic sprayer. In the automatic spray there is an ultrasonic sensor that detects the presence of planthoppers or other insects. When insects are detected, planthoppers are sprayed using direct contact insecticides. This technique is expected to kill planthoppers and reduce planthopper populations quickly and precisely. The application of pest control tools was carried out in Sumbersari village, Srono sub-district, Banyuwangi district.